The validity of an experiment testing the influence of acceleration on time dilation using a rotating Mössbauer absorber and a Synchrotron Mössbauer Source. (15th February 2019) - Friedman, Y.; Steiner, J. M.; Livshitz, S.; Perez, E.; Nowik, I.; Felner, I.; Wille, H.-C.; Wortmann, G.; Efrati, O.; Finkelstein, A.; Petitgirard, S.; Chumakov, A. I.; et al.
Abstract : An indispensable plan, requirements and challenges to overcome for a conclusive experiment to test time dilation due to acceleration, based on three experiments at ESRF, is presented. Abstract : Three experiments are reviewed, performed (in 2014–2016) at ID18 of ESRF to measure the influence of acceleration on time dilation by measuring the relative shift between the absorption lines of two states of the same rotating absorber with accelerations anti‐parallel and parallel to the incident beam. Statistically significant data for rotation frequencies up to 510 Hz in both directions of rotation were collected. For each run with high rotation, a stable statistically significant `vibration‐free' relative shift between the absorption lines of the two states was measured. This may indicate the influence of acceleration on time dilation. However, the measured relative shift was also affected by the use of a slit necessary to focus the beam to the axis of rotation to a focal spot of sub‐micrometre size. The introduction of the slit broke the symmetry in the absorption lines due to the nuclear lighthouse effect and affected the measured relative shift, preventing to claim conclusively the influence of acceleration on time dilation. Assuming that this loss of symmetry is of first order, the zero value of the relative shift, corrected for this loss, falls always within the experimental error limits, as predicted by Einstein's clock hypothesis. The requirements and an indispensable plan for a conclusive experiment, once the improved technology becomes available, is presented. This will be useful to future experimentalists wishing to pursue this experiment or a related rotor experiment involving a Mössbauer absorber and a synchrotron Mössbauer source.